Review: Psychological intervention in temporomandibular disorders. - Pamela Araneda; Juan Fernando Oyarzo; Mariella González; Camilo Figueroa (Universidad de Concepción., 2013)
Patients with temporomandibular disorders (TMD) frecuently present psychological and psychiatric problems. These patients often show increased somatization, depression, anxiety, stress reaction and catastrophism, wich plays a role in the predisposition, initiation and perpetuation of TMD and treatment response. This review presents thaerapeutic options that compromise the psychological axis of patients with TMD, wich primarily seek to reduce the anxiety and the emotional stress present, modify different perceptions of pain and coping. There are different posibilities, within wich are: patient education, identifying situations that increase the tension to avoid them, teaching relaxation techniques such as biofeedback, hipnosis and yoga. As for psychological treatment, the most common for chronic orofacial pain is cognitive behavioral therapy (CBT). The appropriate and effective psychological intervention can reduce TMD pain, decreasing the probability that the symptoms become more complex. Within psychological treatment options for TMD, conservative standard treatment (education, self-instruction, avoidance of painful movements, soft diet), even the shortest, may be sufficient in the short term for most patients with TMD, especially in cases of acute conditions. The addition of CBT, by a specialist, gives coping skills that will add to the effectiveness, especially in chronic cases, obtaining better results in the long term.